2019
DOI: 10.11591/ijece.v9i1.pp426-438
|View full text |Cite
|
Sign up to set email alerts
|

Topic Discovery of Online Course Reviews Using LDA with Leveraging Reviews Helpfulness

Abstract: Despite the popularity of the Massive Open Online Courses, small-scale research has been done to understand the factors that influence the teaching-learning process through the massive online platform. Using topic modeling approach, our results show terms with prior knowledge to understand e.g.: Chuck as the instructor name. So, we proposed the topic modeling approach on helpful subjective reviews. The results show five influential factors: “learn easy excellent class program”, “python learn class easy lot”, “… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 16 publications
(26 reference statements)
0
12
0
Order By: Relevance
“…Table 8 shows papers that reported the sources of the datasets used for conducting experiments along with their corresponding categories and description. Here, the data were mostly collected by conducting surveys among students and teachers or by providing questioners to collect feedback from the students Education/research platforms [14,31,36,40,[44][45][46]48,58,61,70,78,82,84,86,93,95,99,101] This category contains the data extracted from online platforms providing different courses such as Coursera, edX, and research websites such as ResearchGate, LinkedIn, etc.…”
Section: Rq5 What Are the Most Common Sources Used To Collect Students' Feedback?mentioning
confidence: 99%
“…Table 8 shows papers that reported the sources of the datasets used for conducting experiments along with their corresponding categories and description. Here, the data were mostly collected by conducting surveys among students and teachers or by providing questioners to collect feedback from the students Education/research platforms [14,31,36,40,[44][45][46]48,58,61,70,78,82,84,86,93,95,99,101] This category contains the data extracted from online platforms providing different courses such as Coursera, edX, and research websites such as ResearchGate, LinkedIn, etc.…”
Section: Rq5 What Are the Most Common Sources Used To Collect Students' Feedback?mentioning
confidence: 99%
“…Thus, the authors suggested using some mechanism for sampling method to modify imbalanced data into balanced distribution [15]. In 2019, authors of [16] performed sentiment classification with Lexicon Bing for subjectivity classification and LDA for topic modelling. However, the approach only used a lexicon-based approach for subjectivity classification, which might not be reliable for subjectivity detection as the biggest downside of the rule-based method is that the procedure only cares about individual words and lacks the context in which it is used [16].…”
Section: Sentiment Analysis With Subjectivity Classificationmentioning
confidence: 99%
“…In addition to manual coding methodologies and questionnairebased surveys, a mainstream of automatic text mining approaches for MOOC learner satisfaction research is topic models [4,5,[13][14][15]), which, with the basis of term co-occurrences, have topics (i.e., collections of terms with high co-occurrence probabilities) as outputs [16,17]. A topic modeling analysis of 50 MOOCs [5] indicates that "learners focus more on course-related content with positive sentiment and course logistics and video production with negative sentiment (p. 670). "…”
Section: Literature Reviewmentioning
confidence: 99%
“…Such subjective biases lead to difficulties in result replication, and the limited sample sizes cause results to be less comprehensive. As such, computer-based text mining approaches like probabilistic topic models for textual course review analysis in MOOC learner (dis) satisfaction research are becoming increasingly important (e.g., [4,5]). However, the traditional way of applying topic models focuses primarily on negative reviews, leading to the potential danger of mixing the positive sides since reviewers usually do not complain from the beginning to the end in writing a negative review.…”
Section: Introductionmentioning
confidence: 99%